Reimagining Engagement in Dementia Care: Insight From a Community-Based Ukulele Learning Program - Jason Jincheng Fu; Joey Oi Yee Wong; Mario Gregorio; Lillian Hung (Journal of Primary Care & Community Health)
As recognition grows around the need for equitable, person-centered engagement for people living with neurocognitive disorders or dementia, accessible community programs that challenge stigma and foster inclusion remain limited. This program presents a 12-week ukulele learning program co-led by a person living with dementia that advances health equity by promoting inclusion, empowerment, and social connection through music. Developed through a university-community partnership, the program was intentionally designed to welcome participants from diverse cultural backgrounds and cognitive abilities into an accessible and supportive environment. Unlike conventional music-based interventions, the initiative emphasized active skill development, co-leadership, and intergenerational collaboration. Qualitative reflections from the program leads and team members identified 4 key themes: (1) confronting stigma and reimagining capacity; (2) fostering social inclusion and connectedness; (3) creating shared joy and respite for care partners; and (4) encouraging mutual learning and support. Participants emphasized the program as transformative in advancing health equity by challenging dominant deficit-based narratives, affirming the strengths of individuals often marginalized in traditional care settings. This initiative offers a scalable model for an inclusive, community-driven approach to enhance quality of life, strengthen relationships among people living with dementia and their care partners, and promote equitable health outcomes for people living with dementia.